Rocket science and spacecraft fundamentals - Furgang, Kathy (From Earth to the stars., 2018)
Explores the history of rockets and spacecraft, the process of launching a spacecraft, and what the future of rockets and spacecraft might look like. Provides information on the basics of rocket science, such as Newton's third law, propellants, and the parts of a rocket. Includes sidebars, a glossary, and resources for further information.